Carga de trabalho e produto do cuidar em Enfermagem na movimentação intra-hospitalar de pacientes - Campos, Mariana Santos de (2023)
Objetivos: To examine the Nursing viewpoint regarding the implications of the patients´ movement on the work organization as well as the delivery of care at the end of the work shift. Method: A mixed sequential exploratory strategy, carried out in two stages; one qualitative (1) and the other quantitative (2), with equal weighting and based on the theory of transitions. Five units were investigated: medical (stages 1 and 2), surgical (stages 1 and 2), medical-surgical (stage 1) and two specialized - neurology and transplant (stage 2). Four focus groups were set up in the qualitative stage, twenty-three professionals have participated (12 nurses, eight technicians and three nursing assistants) from a school hospital in the state of São Paulo. The reports were analyzed using thematic analysis with the help of MAXQDA software. The design of the quantitative stage was characterized as cross-sectional descriptive, with a non-probabilistic sample for convenience comprising 220-days shifts. Sixteen nurses applied the Assessment of the Product of Nursing Care (APROCENF) scale. Descriptive statistics, the Chi-square test and multiple logistic regression (p≤0.05) were used for analysis. Data were collected in November 2021 and March 2022 (stage 1) and August, September, and October 2022 (stage 2). Data were matched in the collection phase and in the analysis of the findings. Integration was carried out at the end of the analysis. Results: Two thematic categories were obtained: (1) The influence of structural factors and work organization on the intra-hospital movement of patients and (2) The movement of patients takes time, creates work overload, and interferes with the delivery of care (stage 1). During the study period there were 768 in-hospital patient movements; 42.3% of the shifts presented four or more movements. There was a predominance of good ratings for the product of care 158 (71.8%). Statistically significant associations (p<0.001 and p=0.033) were found between the movement of patients, the dimensioning of the team and the product of care for most of the variables. In situations with 2-12 movements/shift and 3.1 - 5.2 patients/professional, there was a 7.35 times chance (95%CI = 3.24 - 16.65) of the product of care being non-optimal; and in the transplant unit 0.42 times (95%CI = 0.20 - 0.88). Conclusion: According to the team's perception, the volume and simultaneous occurrence of patient´s movements, unforeseen demands, complexity of care and insufficient staffing/resources have repercussions on the delivery of care. It was shown that when nurses deal with between three and five patients per professional and, simultaneously, there are between two and 12 intra-hospital movements in the work shift, the possibility of the care product being non-optimal is 7.35 times higher when compared to more favorable situations. The analysis based on the Transitions Theory is an innovative aspect of this study. These findings make it possible to improve the regulation of patients coming to and leaving the units, the organization of work and the management of care. The importance of incorporating admissions, discharges, and transfers into the measurement of workload, planning and distribution of staff and resources to minimize risks to patient and occupational safety can be pointed out.